A Comparison of Policies for International Education between Taiwan and South Korea - Huang, Yueh-Chun; Wang, Ru-Jer (Advances in Social Sciences Research Journal, 2022)
In the face of globalization, Taiwan and South Korea promote international education in primary and secondary schools. The authors conduct a comparative study of international education and its policies in Taiwan and South Korea based on relevant theories and literature. This paper is based on the part of the findings from the comparative study. The purpose of the comparative study was to examine the similarities and differences in the international education policies of Taiwan and South Korea under different social and cultural environments. For the above purpose, methods used include document analysis and comparative research. Concluding remarks are made based on the results of the comparison of policies for international education between Taiwan and Korea.